Analisis Hukum Islam Terhadap Sistem Pengupahan Jasa Urut Tradisional (Studi Kasus di Kelurahan Rano Kecamatan Muara Sabak Barat - Rhodiah Almunawwarah; Zaenal Abidin; Alisyah Pitri; Nilfatri Nilfatri; Zeni Sunarti; Reza Okva Marwendi; Haeran Haeran (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the practice of the traditional massage service wage system in Rano Village, West Sabak District, East Tanjung Jabung Regency, and examine it from an Islamic legal perspective. The focus of the study is directed at two main problems, namely: (1) how the practice of traditional massage service wages is carried out by the community in Rano Village, and (2) how Islamic law views the clarity of the contract (ijarah) and the fairness of wages in this practice. This study uses a descriptive qualitative approach with a case study research method and uses data collection methods through observation, in-depth interviews, and documentation. The results of the study indicate that the majority of transactions are carried out verbally and are not accompanied by an initial nominal agreement, but rather based on the principle of willingness and local customs (‘urf). Normatively, this practice contains elements of gharar which can affect the validity of the contract, but is still tolerable in the socio-cultural context of the community provided it does not give rise to disputes.